The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/app12157616
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Adiposity Increases Lordosis and Doubles the Risk of Low Back Pain

Abstract: Vertebral disorders have significant health and economic impacts, and due to aging and current lifestyle habits, there is a trend toward their increase. Obesity and the alignment of vertebral curvatures can be associated with back pain. Objective: This study aims to analyze whether general and abdominal obesity are associated with cervical, dorsal, and lumbar vertebral pain as well as increased or decreased values of cervical, dorsal, and lumbar vertebral curvatures. Methodology: Body composition, degree of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…This finding is in agreement with a previous study conducted in Iran, Zahedan city, which revealed that fat drivers with high BMI were found associated with the low level of lower back pain in lower back regions 38. However, there is evidence that indicates a strong association between abdominal obesity and LBP as central obesity increases lordosis and doubles the risk of LBP 39 40. There is also evidence that overweight/obesity is a risk factor for LBP41–44 However, other literature reported as the association of overweight/obesity with LBP remains controversial and inconsistent result 45.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in agreement with a previous study conducted in Iran, Zahedan city, which revealed that fat drivers with high BMI were found associated with the low level of lower back pain in lower back regions 38. However, there is evidence that indicates a strong association between abdominal obesity and LBP as central obesity increases lordosis and doubles the risk of LBP 39 40. There is also evidence that overweight/obesity is a risk factor for LBP41–44 However, other literature reported as the association of overweight/obesity with LBP remains controversial and inconsistent result 45.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the android-type overweight group demonstrated a significantly greater lumbar Cobb angle than the normal weight group. These findings are consistent with previous research, which has shown that excessive body weight and adiposity in the abdominal region have a significant impact on the lumbar lordosis curve (Saludes et al, 2022). An increase in body fat percentage in the abdominal region may increase burden on the lumbar spine, shift the CoM forward and increase lumbar lordosis (Romero-Vargas et al, 2013;Sheng et al, 2017).…”
Section: Changes In Spinal Alignmentsupporting
confidence: 92%